Eastern equine encephalitis virus: Pathogenesis, immune response, and clinical manifestations - Bhumika Parashar; Rishabha Malviya; Sathvik Belagodu Sridhar; Tarun Wadhwa; Sirajunisa Talath; Javedh Shareef (Infectious Medicine)
Eastern equine encephalitis virus (EEEV) is a lethal Alphavirus transmitted by Culiseta melanura mosquitoes that primarily cycles between birds. Although rare, infections in humans and horses are associated with high mortality rates and severe neurological effects. Climate change appears to be increasing the spread of this virus. This study aims to provide a comprehensive analysis of EEEV, including its transmission dynamics, pathogenesis, induced host immune response, and long-term impacts on survivors. It also highlights the virus's unique immune evasion strategies that complicate disease management and contribute to severe clinical outcomes, such as encephalitis with fever, convulsions, and coma. Survivors often face chronic cognitive, motor, and psychosocial impairments. Despite these significant public health risks, gaps remain in understanding the molecular mechanisms underlying immune evasion and the long-term neurological sequelae in survivors. By collating current knowledge, this review underscores the urgent need for the development of targeted vaccines and therapeutic interventions to mitigate the growing threat of EEEV, particularly in the context of climate change-driven geographical expansion.